Life Skill Profile of Residents Learning Package C at PKBM Serang District and Its Implications for the Guidance and Counseling Program (Research A Descriptive Study on Residents Learning Package C in PKBM Serang Distrsict in the Academic Year 2021-2022) - Dalimunthe, Raudah Zaimah (Bisma The Journal of Counseling, 2021)
This research aims at describing the illustration of life skill level in thelearning community and discovering the design of the Guidance and Counseling Program to improve life skill on Residents Learning Package C at PKBM Serang District, Indonesia. The survey takes census samples which amounts to 86 learning Residents. The life skill scale was carried out by looking at four aspects, namely personal skills, academic skills, social skills, and vocational skills.Data analysis is performed by descriptive quantitative technique. The result of the questionnaire analysis on the life skills level on Residents Learning Package C atPKBM in Serang District were in low category with a percentage of 20%, the medium category with a percentage of 68%, and the high category with a percentage of 12%. After discovering the description of the life skill level, the design of the Guidance and Counseling Program was made based on the research results obtained.